2022
DOI: 10.1038/s41598-022-14053-9
|View full text |Cite
|
Sign up to set email alerts
|

The histone H2B Arg95 residue links the pheromone response pathway to rapamycin-induced G1 arrest in yeast

Abstract: Rapamycin is an immunosuppressant used for treating many types of diseases such as kidney carcinomas. In yeast, rapamycin inhibits the TORC1 kinase signaling pathway causing rapid alteration in gene expression and ultimately cell cycle arrest in G1 through mechanisms that are not fully understood. Herein, we screened a histone mutant collection and report that one of the mutants, H2B R95A, is strikingly resistant to rapamycin due to a defective cell cycle arrest. We show that the H2B R95A causes defects in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Rapamycin is an immunosuppressant used in organ transplants and for treating various cancers. It acts by inhibiting the TOR kinase pathway and mimicking starvation conditions leading to cell cycle arrest in the G1 phase [ 29 , 30 , 31 ]. We performed spot test and growth curve analyses with rapamycin under similar conditions as for CHX, and found that the agp2Δ mutant showed normal WT resistance to rapamycin, excluding the possibility that Agp2 is involved in the recognition of a broad array of drugs ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rapamycin is an immunosuppressant used in organ transplants and for treating various cancers. It acts by inhibiting the TOR kinase pathway and mimicking starvation conditions leading to cell cycle arrest in the G1 phase [ 29 , 30 , 31 ]. We performed spot test and growth curve analyses with rapamycin under similar conditions as for CHX, and found that the agp2Δ mutant showed normal WT resistance to rapamycin, excluding the possibility that Agp2 is involved in the recognition of a broad array of drugs ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Drugs were added to the cells at the indicated concentrations and growth was monitored for 24 h in a TECAN plate reader with shaking. The temperature was set to 30 °C and the OD was taken every 2 h. The result was plotted as a graph of OD 600 against the time (Sulaiman et al, 2022). For HU sensitivity, the spot test was performed as above.…”
Section: Qxn and Hu Sensitivities Of The Single And Double Mutantmentioning
confidence: 99%
“…One approach to understanding the mechanism of action of QXN is to take advantage of the available tools in the budding yeast Saccharomyces cerevisiae (Sulaiman et al, 2022;Mohanty et al, 2023;Sulaiman et al, 2023). These include a collection of ~4,800 haploid mutants, each deleted for a single non-essential gene.…”
Section: Introductionmentioning
confidence: 99%